Influence of Component Properties on the Photovoltaic Performance of Monolithic Perovskite/Organic Tandem Solar Cells: Sub‐Cell, Interconnecting Layer, and Photovoltaic Parameters. Issue 4 (13th February 2023) - Xie, Yue‐Min; Yao, Qin; Yip, Hin‐Lap; Cao, Yong
Abstract: Wide‐bandgap perovskite sub‐cells (WPSCs)‐based tandem solar cells attract considerable interest because of their capability to surpass the Shockley–Queisser limit. Monolithic perovskite/organic tandem solar cells (POTSCs) integrating WPSCs and small‐bandgap organic sub‐cells (SOSCs) are famous compositions owing to their simple fabrication method and compatibility with flexible devices. Most studies on POTSCs focus on enhancing device efficiency by modifying one or two of the device components (WPSCs, SOSCs, and interconnecting layers). The characteristics of POTSCs are not extensively investigated so far, especially in terms of the influence of the device structure and component properties on the tandem device photovoltaic performance. In this study, the existing p–i–n type WPSC‐based p–i–n POTSCs and n–i–p type WPSC‐based n–i–p POTSCs are reviewed and their advantages and limitations are highlighted. Furthermore, the influence of the tandem device component properties (optical, electrical, and photovoltaic properties) on the photovoltaic parameters (open‐circuit voltage, short‐circuit current density, fill factor, and power conversion efficiency) and the existing device modification methods are discussed to provide comprehensive guidance for the development of POTSCs. Abstract : The influence of device structures and components (wide‐bandgap perovskite sub‐cells, small‐bandgap organic sub‐cells, and interconnecting layers) properties on the monolithic perovskite/organic tandem solar cells (POTSCs) photovoltaic parameters (open‐circuit voltage, short‐circuit current density, fill factor, and power conversion efficiency) are comprehensively reviewed. This work consolidates the research on POTSCs and provides new inspirations for the further development of POTSCs.